2017
DOI: 10.1590/s0100-204x2017000700008
|View full text |Cite
|
Sign up to set email alerts
|

Soil physico-hydraulic properties under organic conilon coffee intercropped with tree and fruit species

Abstract: The objective of this work was to evaluate the cultivation effects of organic conilon coffee (Coffea canephora) intercropped with tree and fruit species on soil physico-hydraulic properties. Conilon coffee managements in the organic system were: T1, full-sun monoculture; T2, T3, T4, and T5, intercropping with peach palm (Bactris gasipae), gliricidia (Gliricidia sepium), banana (Musa sp.), and inga (Inga edulis), respectively; and T6, an area of secondary native forest used as a control. The evaluated soil phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 22 publications
2
16
0
3
Order By: Relevance
“…By 1845, Brazil was already the world's largest coffee producer, a position it maintains to this day (USDA, 2019). Almost all Brazilian coffee production comes from plantations with full sunlight conditions (Aguiar‐Menezes et al., 2007; Jaramillo‐Botero, Santos, Martinez, Cecon, & Fardin, 2010; Mancuso, Soratto, & Perdoná, 2013; Souza et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By 1845, Brazil was already the world's largest coffee producer, a position it maintains to this day (USDA, 2019). Almost all Brazilian coffee production comes from plantations with full sunlight conditions (Aguiar‐Menezes et al., 2007; Jaramillo‐Botero, Santos, Martinez, Cecon, & Fardin, 2010; Mancuso, Soratto, & Perdoná, 2013; Souza et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In high-altitude broadleaved forests, coffee flourishes under mild understory conditions (Wrigley, 1988). Coffee was brought to Brazil in 1727, and as early as 1731, there were reports of the first exports of coffee have been found with shade tree intercropping in coffee plantations, such as: increased air humidity (Araújo, Partelli, Oliosi, & Pezzopane, 2016;Partelli et al, 2014); increased soil organic matter (Melloni et al, 2018); lower soil density, penetration resistance, and higher total porosity, microporosity, and soil water content (Souza et al, 2017); decreased nutrient leaching, improved soil fertility, and reduced fertilizer requirements (Babbar & Zak, 1995;Cuenca, Aranguren, & Herrera, 1983;Fassbender, 1987;Jaramillo-Botero et al, 2010); reduced incidence of Cercospora coffeicola (Berkeley & Cooke;Salgado, Macedo, Carvalho, Salgado, & Venturin, 2007), Leucoptera coffeella (Guérin-Mèneville & Perrottet; Teodoro, Klein, Reis, & Tscharntke, 2009), several species of fruit flies (Diptera: Tephritoidea; Aguiar-Menezes et al, 2007), and weeds (Concenço et al, 2014;Silva, Perdoná, Soratto, & Negrisoli, 2013); as well as improvement in the quality of the harvested coffee beans (Vaast, Bertrand, Perriot, Guyot, & Génard, 2006). On the other hand, the following disadvantages can be noted: lower soil moisture in the dry season (Coelho, Matsumoto, Lemos, & Souza, 2010;Neves, Martinez, Souza, & Cecon, 2007), higher incidence of Hypothenemus hampei (Ferrari; Wrigley, 1988), need for pruning to regulate shading provided by trees to coffee plants, and, mainly, limitation of coffee production potential and mechanized cultural practices, especially mechanized coffee harvesting (Perdoná & Soratto, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In a coffee area intercropped with tree species and fruit trees, Souza et al (2017) found lower temperature and higher humidity, compared to the treatment in which this practice was not used (monoculture, under full sun), where the former conditions favored the plant development.…”
Section: Resultsmentioning
confidence: 80%
“…Furthermore, roots in both AF systems were better distributed if compared to those in the OG profile, revealing their better soil structure. This is mainly due to presence of biopores and their connectivity and continuity that are greater than in structural pores (Souza et al, 2017), as well as by presence of roots.…”
Section: Soil Penetration Resistance (Pr)mentioning
confidence: 99%